2000
DOI: 10.1046/j.1471-4159.2000.740508.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Matrix Metalloproteinase MMP‐9 (92‐kDa Gelatinase) by Retinoic Acid in Human Neuroblastoma SKNBE Cells

Abstract: Retinoic acid (RA) has been shown to induce human neuroblastoma SKNBE cell differentiation into a neuronal phenotype. Whether this neuronal differentiation is associated with modulation of matrix gelatinase [matrix metalloproteinase (MMP)-2 and MMP-9] expression was investigated in SKNBE cell cultures exposed to RA for 14 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 43 publications
2
58
0
Order By: Relevance
“…However, the mechanism underlying N-Myc repression of MMP-9 is unclear. In neuroblastoma, the induction of di erentiation leads to MMP-9 upregulation (Chambaut-Guerin et al, 2000). Our hypothesis is that NMyc expression leads to a less di erentiated phenotype, which allows the cells to increase growth and motility.…”
Section: Discussionmentioning
confidence: 92%
“…However, the mechanism underlying N-Myc repression of MMP-9 is unclear. In neuroblastoma, the induction of di erentiation leads to MMP-9 upregulation (Chambaut-Guerin et al, 2000). Our hypothesis is that NMyc expression leads to a less di erentiated phenotype, which allows the cells to increase growth and motility.…”
Section: Discussionmentioning
confidence: 92%
“…Of these different cell types, only the 'N'-type cells possess tumorigenic potential and play an important role during tumor metastasis (Biedler et al, 1988;Ciccarone et al, 1989). Effects of RA on 'N'-type neuroblastoma cells are variable; the RAsensitive cells differentiate, quit cell cycle and migrate to form cell aggregates resembling ganglia, while differentiation-resistant cells show increased invasion (Chambaut-Guerin et al, 2000;Farina et al, 2002). Also, under normal conditions, RA plays an important role in the development of nervous system and migration of neural crest cells (Maden and Holder, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Early work in the field suggested that metalloproteinases play a largely permissive role in axon outgrowth -by degrading the ECM in order to clear a path for extending axons (Muir, 1994;Nordstrom et al, 1995;Zuo et al, 1998). In support of a role for MMPs in outgrowth, it has been shown that a number of MMPs are expressed on the growth cones of vertebrate neurites extending in vitro (Chambaut-Guerin et al, 2000;Hayashita-Kinoh et al, 2001;Nordstrom et al, 1995;Zuo et al, 1998). More recent work has demonstrated that in vitro, metalloproteinases are capable of modulating the interactions between guidance cues and their receptors (Galko and Tessier-Lavigne, 2000;Hattori et al, 2000).…”
Section: Metalloproteinases Serve Constructive Functions In the Cnsmentioning
confidence: 99%